Sifat Fisik Kombinasi Mikroorganisme Lokal - Riama Rita Manulang (Jurnal Loupe, 2017)
Local microorganisms (MOL) are microorganism that are used as bio activators in the producing solid and liquid organic fertilizer. The main components of local microorganism are carbohydrates, glucose, and microorganism sources. The research was conducted based on two reasons: (1) the fact that many fruit waste was left unused, for instance, deserted banana sticks, golden snail which considered as a pest to crops, cattle rumen, and (2) the need to reduce dependability on anorganic fertilizer by exploring the role of microorganism. The objective of this research was to produce mol liquid which can be used as bio activator as well as liquid organic fertilizer. The materials used in this production were banana sticks, fruit waste, golden snail, cow rumen, cow urine, coconut water, rice water (lery), shrimp paste, brown sugar for MOL I. MOL II used the same materials except for brown sugar which was substituted with white sugar. MOL was produced through fermentation. The production of MOL was done in the Production Laboratory at State Agricultural Polytechnic of Samarinda. Based on the observation, the combination of MOL was well fermented on day ten. This was shown by dark brown color, stablized temperature, tape smell, and the sight of thin fibre on the mol surface.